2017
DOI: 10.1021/acs.jpca.7b09833
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Two Conformers of Acrylic Sulfuric Anhydride by Microwave Spectroscopy

Abstract: The rotational spectrum of acrylic sulfuric anhydride (CH═CHCOOSOOH, AcrSA) has been observed using pulsed-nozzle Fourier transform microwave spectroscopy. The species was produced from the reaction between acrylic acid and sulfur trioxide in a supersonic jet. Spectroscopic constants are reported for both the s-cis- and s-trans-AcrSA conformers of the parent and monodeuterated (OD) isotopologues. Geometries were optimized for both conformers using M06-2X/6-311++G(3df,3pd) methods. Single-point energy calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…In TS1 and TS2, −COOH and −SO form a six-membered ring, analogous to the transition state structures of the reactions between SO 3 and some carboxylic acids. [29][30][31]48 The Gibbs free energies of TS1 and TS2 relative to their corresponding prereaction complexes, i.e., Gibbs free energy barriers, are 3.12 and 2.56 kcal/mol, respectively, meaning that these reactions can rapidly occur once GA collides with SO 3 in the atmosphere. The Gibbs free energy barriers also indicate that this kind of reaction seems general for carboxylic acids and is almost not affected by the adjacent aldehyde group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In TS1 and TS2, −COOH and −SO form a six-membered ring, analogous to the transition state structures of the reactions between SO 3 and some carboxylic acids. [29][30][31]48 The Gibbs free energies of TS1 and TS2 relative to their corresponding prereaction complexes, i.e., Gibbs free energy barriers, are 3.12 and 2.56 kcal/mol, respectively, meaning that these reactions can rapidly occur once GA collides with SO 3 in the atmosphere. The Gibbs free energy barriers also indicate that this kind of reaction seems general for carboxylic acids and is almost not affected by the adjacent aldehyde group.…”
Section: Resultsmentioning
confidence: 99%
“…Mackenzie et al have observed the gas-phase barrierless reaction between formic acid and SO 3 to form formic sulfuric anhydrides . In addition, acetic acid and acrylic acid were also found to react with SO 3 to form corresponding carboxylic sulfuric anhydrides through barrierless reactions, indicating that some hydrocarbon substituent groups, such as −CH 3 and −CHCH 2 , have little effect on the reaction between the carboxyl group and SO 3 . , These products all have stronger acidities and lower vapor pressures compared with those of their corresponding carboxylic acids, and therefore, they are much more likely to participate in nucleation. Thus, it might be an underlying way for RCOOH (R indicates hydrocarbon group) to participate in nucleation by transferring itself to the corresponding carboxylic sulfuric anhydride with a greater nucleation potential by reacting with SO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This reaction also involves a low free‐energy barrier of activation (2.5 kcal mol −1 for FA, Figure S1). It provides a mechanism for incorporating organic matter into aerosol particles …”
Section: Figurementioning
confidence: 99%
“…It seems that the nucleation ability of carboxylic acid could be improved by the reaction with SO 3 , and the corresponding product carboxylic sulfuric anhydride is speculated to participate in NPF . The subsequent theoretical calculation on monocarboxylic acids suggested that different types of substituents such as −CHCH 2 , −CCH, −CF 3 , and the aldehyde group have little effect on the reaction energy barrier, ,, while for polycarboxylic acids, the energy barriers of reactions between one SO 3 and −COOH at different sites are all low enough for these reactions to take place in the gas phase . However, the kinetics of the sequential reaction of multiple −COOH with multiple SO 3 and their influence on NPF are still unclear.…”
Section: Introductionmentioning
confidence: 99%